EFEKTIFITAS KAPSUL EKSTRAK DAUN KATU DAN DAUN KELOR TERHADAP KECUKUPAN ASI PADA BAYI KURANG DARI 6 BULAN DITINJAU DARI BERAT BADAN BAYI DI KLINIK BD. ROSITA PEKANBARU - Fajar Sari Tanberika; Rika Ruspita; Rifa Rahmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The postpartum period is the time that starts when the baby is born and the baby's placenta is born until the uterus returns to the state it was before pregnancy. This period usually occurs around 6 weeks. Breastfeeding is a unique way of providing food that is ideal for the healthy growth and development of babies and has a unique biological and psychological effect on the health of both mother and baby. The anti-infective substances contained in breast milk help protect babies against disease (Anggaini Y, 2010). The aim of this study was to determine the adequacy of breast milk in infants under 6 months seen from the baby's weight gain. The type of research used in this research is the Pre-Experimental research method with a Static Group Comparison design where in this research design there is an experimental group and a control group. The experimental group received treatment (X) followed by a second measurement or observation (02). The results of these observations were then controlled or compared with the results of observations in the control group, which did not receive any programs or interventions (Notoatmodjo, 2012). The location in this study will be held at the Rosita Midwife Clinic in Pekanbaru. The population in this study were all mothers and babies under 6 months who were breastfeeding at the Rosita Midwife Clinic. The sampling technique is by means of purposive sampling which is based on a certain consideration and based on the nature and characteristics of the previously known population. The number of research samples was 15 postpartum mothers who were breastfeeding, using univariate and bivariate data analysis.